Taxonomy and phylogenetics of Tmesiphantes Simon, 1892 (Araneae, Theraphosidae). Issue 7 (3rd October 2019) - Fabiano-Da-Silva, Willian; Guadanucci, José Paulo Leite; Dasilva, MArcio Bernardino
Abstract : The tarantula genus Tmesiphantes Simon, 1892 (Theraphosinae) includes nine valid species, with records for the states of Bahia ( T. nubilus, T. caymmii, T. amadoi, T. bethaniae, T. hypogeus, and T. mirim ), Minas Gerais ( T. perp and T. riopretano ), and Pará ( T. aridai ), all in Brazil. In the present study, we reviewed the taxonomy of the Tmesiphantes species and performed a phylogenetic analysis using morphological characters. Four new species are described: T. amazonicus sp. nov., T. guayarus sp. nov., T. nordestinus sp. nov., and T. raulseixasi sp. nov., which expand the geographic distribution for the following states in Brazil: Goiás, Mato Grosso, Piauí, Paraíba, and Pernambuco, occurring in the Caatinga shrublands Cerrado savannas, Atlantic rain forest, and Brazilian Amazon. Phylogenetic analysis included 30 terminal taxa and 37 characters, including representatives of nine genera of Theraphosinae. The Tmesiphantes species formed a monophyletic group with the species hitherto included in Melloleitaoina and Magulla, with the latter being paraphyletic, which led us to propose the synonymy of these three genera. An updated diagnosis is proposed for the genus Tmesiphantes, which now comprises 19 species, occurring in major Brazilian biomes and in Argentina. A distribution map that includes all Tmesiphantes species and notes on their distributions are provided.